The Role of Vessel Biofouling in the Translocation of Marine Pathogens: Management Considerations and Challenges - Georgiades, Eugene; Scianni, Chris; Davidson, Ian; Tamburri, Mario N.; First, Matthew R.; Ruiz, Gregory; Ellard, Kevin; Deveney, Marty; Kluza, Daniel (Frontiers in Marine Science, 2021)
Vessel biofouling is a major pathway for the introduction, establishment, and subsequent spread of marine non-indigenous macro-organisms. As a result, national and international regulations and guidelines have been implemented to manage the risks associated with this pathway, yet widespread enforcement and uptake are still in their infancy. By comparison, translocation of marine pathogens by vessel biofouling has received little attention despite a mounting body of evidence highlighting the potential importance of this pathway. Using molluscan pathogens as a model, this paper examines the potential for translocation of marine pathogens via the vessel biofouling pathway by reviewing: (1) examples where vessel biofouling is suspected to be the source pathway of non-indigenous pathogen introduction to new areas, and (2) the association between pathogens known to have detrimental effects on wild and farmed mollusk populations with species known to foul vessels and anthropogenic structures. The available evidence indicates that vessel biofouling is a viable and important pathway for translocating marine pathogens, presenting a risk to marine values (i.e., environmental, economic, social, and cultural). While preventive measures to minimize the translocation of macro-organisms are the most efficient way to minimize the likelihood of associated pathogen translocation, the application of reactive management measures to biofouled vessels, including post-filtration treatment, requires further and explicit consideration.